264. Anti-platelet Therapy Significantly Reduces Inpatient Mortality in Patients with Staphylococcus aureus Bacteremia. (31st December 2020) - Caffrey, Aisling; O'Neill, Emily T; Lopes, Vrishali; Ulloa, Erlinda R; Sakoulas, George; Nizet, Victor; LaPlante, Kerry
Abstract: Background: There is a growing body of evidence which suggests that P2Y12 inhibitors may have antibacterial properties in vivo. To our knowledge, this has not been previously examined using real world clinical data from patients with specific infections. Methods: Our retrospective cohort study included patients admitted to Veterans Affairs hospitals between 2010–2018 with blood cultures positive for S. aureus and treated with appropriate antibiotics within 48 hours of culture collection. We included patients treated with P2Y12 inhibitors for at least the 30 days prior to admission and continued use for at least 5 days after admission. Non-users included patients without P2Y12 inhibitor use in the year prior to admission through discharge. We compared clinical outcomes during the S. aureus bacteremia admission among P2Y12 users and non-users using propensity score matched Cox proportional hazards regression models. Results: We identified 371 P2Y12 inhibitor users (clopidogrel, prasugrel, ticagrelor, cangrelor) and 13, 298 non-users. Mean age was 70 years and 69 years, respectively. Over 98% were male in both the groups, and the overall inpatient mortality rate was 8.7%. We were able to match 199 users and non-users, which were well matched in terms of baseline covariates. Inpatient mortality was significantly lower among P2Y12 inhibitor users (hazard ratio [HR] 0.08, 95% confidence interval [CI] 0.01–0.64), and 30-day mortality was non-significantly lower (HR 0.57, 95% CI 0.31–1.03). There was no difference between the groups in readmission or re-infection within 30 days of discharge. Conclusion: Among patients with S. aureus bacteremia, those treated with P2Y12 inhibitors in the days leading up to admission and continuing through the initial period of antibiotic treatment, had a 92% lower risk of inpatient mortality. Identifying adjunctive therapies which improve clinical outcomes among patients with S. aureus bacteremia is highly important in order to improve patient outcomes and to increase the understanding of the pathophysiology of the disease. Prospective clinical studies are needed to further define the potential benefits of P2Y12 inhibitors in S. aureus bacteremia and possibly other infection types. Disclosures: Aisling Caffrey, PhD, Merck (Research Grant or Support)Pfizer (Research Grant or Support)Shionogi (Research Grant or Support) Erlinda R. Ulloa, MD, MSc, Cidara Therapeutics (Consultant) Victor Nizet, MD, Centauri Therapeutics (Advisor or Review Panel member)Cidara Therapeutics (Advisor or Review Panel member)InhibRx (Advisor or Review Panel member)Roche Pharmaceutical (Advisor or Review Panel member) Kerry LaPlante, PharmD, Merck (Advisor or Review Panel member, Research Grant or Support)Ocean Spray Cranberries, Inc. (Research Grant or Support)Pfizer Pharmaceuticals (Research Grant or Support)Shionogi, Inc. (Research Grant or Support)